Pembatasan Jangka Waktu Jual Putus (Sold Flat) Hak Cipta Dalam Perspektif Peraturan Perundang-Undangan - Zahira, Ramadhanti; Yahya, Taufik; Zulfa Aulia, M. (Zaaken: Journal of Civil and Business Law, 2026)
The objective of this research is to examine and analyze the regulation of sold flat of copyright from the perspective of the Copyright Law (Undang-Undang Hak Cipta/UUHC) and to understand sold flat in relation to the principles of contract law. This study employs a normative juridical method with a statutory approach (normative approach), conceptual approach, and case approach. The findings indicate that regulation of sold flat is only recognized under Law No. 28 of 2014 and is reinforced by Constitutional Court Decision No. 63/PUU-XIX/2021. This regulation is considered important, as creators invest significant effort and resources into their copyrighted works. However, the sold flat arrangement contradicts Article 1381 of the Civil Code (KUHPer). From the perspective of civil contract law, sold flat agreements tend to disregard the principles of freedom of contract and balance. Ideally, such agreements should be based on the principle of freedom of contract, allowing parties to define terms and time limits, and the principle of balance to ensure no party is harmed. Other relevant principles include pacta sunt servanda, consensual and real agreement, and good faith. It is recommended that the legislature revise Articles 18 and 30 of Law No. 28 of 2014, replacing the term “Sold Flat” with “Copyright Sale and Purchased Agreement”.